Utilization of E-Commerce and Digital Marketing to Increase Value Added Products for MSMEs and Home Businesses in Kerinjing Village - Burhanudin Burhanudin; Yusnaini Yusnaini; Nur Khamisah; Shelly Febriana Kartasari (Faculty of Economics, Universitas Sriwijaya, 2022)
This community service aims to help business actors, both MSMEs and home-based businesses in Kerinjing Village, in the use of E-Commerce and Digital Marketing in order to increase the added value of a product. In the face of increasingly difficult business competition, especially in this COVID-19 pandemic situation, business players need a creative and innovative idea in marketing their products, so that their business can survive. Therefore, this service activity is carried out to provide assistance and training to business players in Kerinjing Village in utilizing E-Commerce and Digital Marketing. Service activities are carried out starting from the introduction and providing an understanding of E-Commerce and Digital Marketing, followed by training on the use of E-Commerce where results of the activities will be monitored and evaluated further. This Community Service activity was attended by 35 participants, consisting of business players and MSMEs in Kerinjing Village.